2021
DOI: 10.1371/journal.pone.0254954
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity during COVID-19 pandemic: A genuine concern for people from disadvantaged community and low-income families in Province 2 of Nepal

Abstract: Background Food insecurity is a serious social and public health problem which is exacerbated by the COVID-19 pandemic especially in resource-poor countries such as Nepal. However, there is a paucity of evidence at local levels. This study aims to explore food insecurity among people from the disadvantaged community and low-income families during the COVID-19 pandemic in Province-2 of Nepal. Methods The semi-structured qualitative interviews were conducted virtually among purposively selected participants (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 34 publications
4
45
1
1
Order By: Relevance
“…Eranga [39] confirmed a trail of lamentations about the lopsided distribution of government palliatives by citizens in Nigeria. In Napal, Singh et al [40] praised the government efforts in responding to the food crisis during the COVID-19 pandemic. They nevertheless pointed out that favoritism, nepotism, poor coordination, and partiality made it difficult for the food-relief distributions to get to vulnerable groups that needed it.…”
Section: Discussionmentioning
confidence: 99%
“…Eranga [39] confirmed a trail of lamentations about the lopsided distribution of government palliatives by citizens in Nigeria. In Napal, Singh et al [40] praised the government efforts in responding to the food crisis during the COVID-19 pandemic. They nevertheless pointed out that favoritism, nepotism, poor coordination, and partiality made it difficult for the food-relief distributions to get to vulnerable groups that needed it.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, their purchasing power decreases, and poor and marginalized families are likely to be affected the most. For example, in Nepal, Singh et al [ 36 ] found that the COVID-19 pandemic caused severe food insecurity among the disadvantaged communities and low-income families that relied on daily wages and remittance income.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, COVID-19 affected both supply and demand of food markets, resulting in higher food prices, leading to food insecurity and poverty in many developing and emerging countries. As mentioned above, various studies have investigated economy-wide impacts of COVID-19 induced turmoil [ 45 , 46 ], effects on labor markets [ 23 , 33 , 47 , 48 ], household income and food security [ 14 , 26 , 28 , 36 , 38 , 49 52 ], and trade flows [ 41 , 53 ]. However, the literature on price effects of the COVID-19 pandemic is minimal.…”
Section: Introductionmentioning
confidence: 99%
“… 28 In Nepal, food insecurity was a serious concern among the low-income and disadvantaged families during the COVID-19, and it severely affected their health and well-being. 29 …”
Section: Discussionmentioning
confidence: 99%